2022
DOI: 10.1371/journal.pgph.0000871
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental health and child nutritional status in an urban slum in Bangladesh: A cross-sectional study

Abstract: Poor mental health may diminish a mother’s capacity to adequately care for her child, resulting in a negative impact on the child’s nutrition. This study aims to determine the association between maternal mental health and child nutritional status in a poor urban population in Bangladesh. We carried out a cross-sectional study among 264 mother-child pairs in an urban slum area of Bangladesh. The Self-Reporting Questionnaire-20 (SRQ-20) was used to assess maternal mental health. An SRQ-20 score ≥7 was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Household food insecurity was shown to be significantly associated with CMD in the current study even when social support and other variables were adjusted for. This observation is in line with the findings of other studies in which maternal mental health status was significantly associated with food security [37,52,55,56]. Concerns over provision of food or household food insecurity or inability to afford basic needs including food may increase cognitive load acting as a stressor and increasing the risk of CMD in mothers [57,58].…”
Section: Association Between Household Food Insecurity and Cmdsupporting
confidence: 91%
“…Household food insecurity was shown to be significantly associated with CMD in the current study even when social support and other variables were adjusted for. This observation is in line with the findings of other studies in which maternal mental health status was significantly associated with food security [37,52,55,56]. Concerns over provision of food or household food insecurity or inability to afford basic needs including food may increase cognitive load acting as a stressor and increasing the risk of CMD in mothers [57,58].…”
Section: Association Between Household Food Insecurity and Cmdsupporting
confidence: 91%
“…Lakatos et al found that 44.8% of moderate to severe depression in cases with infertility, while a high level of anxiety was reported in around 40% of cases. Hasan et al evaluated the mental health status of Bangladeshi women undergoing fertility treatment and reported a high prevalence of depression, anxiety, and stress (59.7%, 55.0%, and 48.7%, respectively) [ 17 ]. Shahraki et al found that women with primary infertility suffered more from depression than those with secondary infertility [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study used a cross-sectional dataset collected to investigate the association between maternal mental health and child nutritional status [ 12 ]. The study was undertaken from September to November 2013 in an urban slum area at Kamrangichar in Dhaka, Bangladesh.…”
Section: Methodsmentioning
confidence: 99%